2013
DOI: 10.4172/2161-0460.1000128
|View full text |Cite
|
Sign up to set email alerts
|

CSF and Brain Indices of Insulin Resistance, Oxidative Stress and Neuro-Inflammation in Early versus Late Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is characterized by progressive impairments in cognitive and behavioral functions with deficits in learning, memory and executive reasoning. Growing evidence points toward brain insulin and insulin-like growth factor (IGF) resistance-mediated metabolic derangements as critical etiologic factors in AD. This suggests that indices of insulin/IGF resistance and their consequences, i.e. oxidative stress, neuro-inflammation, and reduced neuronal plasticity, should be included in biomarker pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 99 publications
3
21
0
Order By: Relevance
“…Our finding that cytokines are activated early in AD but not late in the clinical course is consistent with previous observations [59,70]. It is particularly noteworthy that the pronounced reductions in cytokine activation overlapped with declines in the expression of trophic factor and mediators of insulin signaling/responsiveness, and increases in brain levels of AβPP-Aβ, pTau, and advanced glycation end-products [69]. Indeed, the complexity of cytokine activation profiles in AD CSF has been reported previously [71], perhaps due to time or disease duration related shifts in neuro-inflammation.…”
Section: Consequences Of Brain Insulin/igf Resistance Promote Ad Nsupporting
confidence: 92%
See 1 more Smart Citation
“…Our finding that cytokines are activated early in AD but not late in the clinical course is consistent with previous observations [59,70]. It is particularly noteworthy that the pronounced reductions in cytokine activation overlapped with declines in the expression of trophic factor and mediators of insulin signaling/responsiveness, and increases in brain levels of AβPP-Aβ, pTau, and advanced glycation end-products [69]. Indeed, the complexity of cytokine activation profiles in AD CSF has been reported previously [71], perhaps due to time or disease duration related shifts in neuro-inflammation.…”
Section: Consequences Of Brain Insulin/igf Resistance Promote Ad Nsupporting
confidence: 92%
“…In a recent study, analysis of cerebrospinal fluid (CSF), ventricular fluid (VF) and postmortem brain tissue by multiplex bead-based ELISAs revealed either significantly or moderately elevated levels of at least 15 different cytokines in AD CSF and brains during early or intermediate stages of disease, but broad-based suppression rather than activation of pro-inflammatory mediators in VF and brain tissue during the late stages of AD [69]. Our finding that cytokines are activated early in AD but not late in the clinical course is consistent with previous observations [59,70].…”
Section: Consequences Of Brain Insulin/igf Resistance Promote Ad Nmentioning
confidence: 99%
“…Downstream effects include oxidative stress with increased production of reactive oxygen and reactive nitrogen species which can damage nerve terminals, causing synaptic dysfunction and attendant cognitive impairment [19]. Furthermore, since chronic inflammation is known to exacerbate insulin resistance associated with systemic disease-states [2428], neuro-inflammation could also have an important etiopathic role in the brain insulin and IGF-1 resistances that occur in AD [2934] and Parkinson’s disease [35]. Furthermore, inflammation has inhibitory effects on incretin (orexin) expression and function, while reduced insulin resistance afforded by activation of incretin signaling inhibits pro-inflammatory cytokines such as tumor necrosis factor-alpha (TNF-α) [36].…”
Section: Neuro-inflammationmentioning
confidence: 99%
“…Experimental models have shown that brain insulin resistance or deficiency impair learning and memory [64]. In early or intermediate stages of AD, brain and CSF levels of insulin are decreased [34], while Aβ42 and advanced glycation end-products are increased [34, 54, 93]. High levels of Aβ42 in brain and CSF are associated with low levels in serum due to decreased clearance [94].…”
Section: Brain Metabolic Dysfunction In Admentioning
confidence: 99%
“…A recent and prominent concern has been the role of IR as a factor promoting oxidative stress in the pathogenetic cascade of AD [105, 106]. The term “oxidative stress” refers to an imbalanced biochemical state wherein the cell is producing more reactive oxygen species than its antioxidant activity can withstand [107].…”
Section: Ir and Oxidative Stress In Admentioning
confidence: 99%